2011
DOI: 10.3892/mmr.2011.411
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 -634C>G polymorphism in hypertensive patients with and without left ventricular hypertrophy

Abstract: Abstract.There is an accumulating body of evidence indicating that inflammation plays a pivotal role in the pathogenesis of cardiovascular disease. interleukin-6 (il-6) is a pleiotropic cytokine secreted by many cells of the immune system, cardiovascular components and adipose tissue, and functions as a mediator of inflammatory response with both pro-and anti-inflammatory properties. Circulating levels of IL-6 differ greatly between individuals due to both genetic and environmental factors. The IL-6 -634C>G po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…Then, we found that the additional studies were all replicates from the other databases after we removed the articles that met the exclusion criteria. Finally, 13 articles 11 , 12 , 16 – 18 , 71 78 met all of the inclusion criteria and were enrolled in the meta-analysis, which contained 10 articles in English and 3 articles in Chinese (Figure 1 ), although language was not restricted in the search protocol or practice. Among them, 2 articles provided data regarding both of them; therefore, we considered each article as 2 studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, we found that the additional studies were all replicates from the other databases after we removed the articles that met the exclusion criteria. Finally, 13 articles 11 , 12 , 16 – 18 , 71 78 met all of the inclusion criteria and were enrolled in the meta-analysis, which contained 10 articles in English and 3 articles in Chinese (Figure 1 ), although language was not restricted in the search protocol or practice. Among them, 2 articles provided data regarding both of them; therefore, we considered each article as 2 studies.…”
Section: Resultsmentioning
confidence: 99%
“…Lots of studies have shown that IL-6 levels are positively correlated with blood pressure, 9 , 10 and its genetic polymorphism may have a connection with hypertension. 11 , 12 The gene encoding IL-6 is located at chromosome 7p21 and contains 6 exons with a 1.3-kb coding sequence (size 6119 base pairs). Most studies have focused on the promoter region of the IL-6 gene because many polymorphisms are identified in this region, including −598A/G, −597G/A, −572 C>G, and −174 G>C. Of these polymorphisms, the 2 most commonly involved and researched are −572 C>G and −174 G>C. The polymorphism −572 C>G, known as −634 C>G or 1800796, is at base pair 572.…”
Section: Introductionmentioning
confidence: 99%